ACADEMIC ENTREPRENEUR DEVELOPMENT (MANAGEMENT PTKIS PERSPECTIVE) - Rahman, Kholilur; Fanani, Ahmad Aziz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Recently, the phenomenon of paradigm revolution arised in the management of tertiary institutions (both state or private) to become financially more independent institutions, no longer only rely on funding subsidies from the government, but doing for innovating, exploring, and managing the potential